Aspectos Clássicos da Eletrodinâmica de Podolsky - Ortega, Paulo Henrique [UNESP] (2014)
The Generalized Electrodynamics was developed by Boris Podolsky in 1942 and it is a generalization of Maxwell’s theory where Podolsky added a new term to the Maxwell’s Lagrangean with a second derivative of the electromagnetic ?eld. It was shown that Podolsky’s Electrodynamics is the only possible generalization of a second gauge invariant to Maxwell’s Electrodynamics. In this context, our work aims a study of some classical properties of Podolsky’s Electrodynamics. We study multpole theory in Podolsky’s Electrodynamics applying the results to some examples in Electrostatic and Magnetostatic. We also ?nd the multipolar expansion in this study, which was something that, to our knowledge, has not been done so far. Lastly, we approach the basic concepts of the Radiation Theory and we obtain the Green’s Function of the Podolsky’s Electromagnetic four-potencial and the Liénard-Wiechert-Podolsky’s potentials